Analysis of the Use of Color LUTs in Project Video Announcements - Wahyu Yudianto; Diny Anggriani Adnas (Sean Institute, 2022)
Video evolved into one of the mediums for displaying information that displays sound as well as images for various purposes. There are 3 important stages in the video production process, namely Pre-Production, Production, and Post-Production. In this study, we discuss more deeply the important part that is included in the Post-Production stage, namely Color Grading which is included in the editing stage. Qualitative comparison is a method that the author uses to compare the color grading technique commonly applied by production houses in the film industry with the color grading technique applied to an announcement video project. The results of this research show that this research can be a knowledge and reference in making a video project, because it is proven that the coloring process is an important step to build the look and mood of a video project.